Regional Autonomy in the Indonesian Constitutional System: Between Decentralization and Centralization - Mardona Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Regional autonomy is a strategic policy within the Indonesian state system, aimed at creating an effective, democratic, and responsive government. However, in practice, the implementation of regional autonomy still faces a dynamic tug-of-war between decentralisation and centralisation, giving rise to problems such as overlapping authority, regional fiscal dependence, and a tendency towards recentralization by the central government. Therefore, this study aims to analyse the concept, legal basis, and implementation of regional autonomy in the context of the relationship between the central and regional governments. This study uses normative legal research with a statutory and conceptual approach. Data sources consist of primary legal materials, such as the 1945 Constitution and Law Number 23 of 2014 concerning Regional Government, as well as secondary legal materials in the form of books, scientific journals, and previous research results. Data collection techniques were carried out through literature studies, while data analysis techniques used descriptive qualitative analysis by systematically interpreting and reviewing legal materials. The results of the study indicate that the implementation of regional autonomy in Indonesia is not fully optimal due to the ongoing imbalance between central and regional authorities. In addition, policy inconsistencies were found that trigger a tendency towards re-centralisation. Therefore, it is necessary to harmonise regulations, strengthen regional capacity, and maintain policy consistency to create an ideal balance between decentralisation and centralisation within the framework of the Unitary State of the Republic of Indonesia.